Quality management of sintered aluminum powder (SAP) composite alloy - Макаренко, Дмитрий Николаевич (Technology audit and production reserves, 2014)
This article is devoted to the research of dispersion-strengthened composite materials based on aluminum such as SAP to ensure their quality management. The orthogonal central composite design is used to analyze the composition and properties of aluminum-based DSCM. The mathematical models depending of the elongation and tensile strength of the various SAP on the temperature and the content of aluminum oxide Al2O3 are built. Analysis of the mathematical models of obtained response surfaces showed that the tensile strength for SAP is most dependent on the temperature of the test sample (operating temperature) and Al2O3 content does not impact. As for the elongation of the samples, it is almost equally as dependent on the temperature of the test (operation), and the content of Al2O3. It has been established that the increase in the Al2O3 content and the temperature of test samples leads to decrease of tensile strength and elongation of aluminum-based DSCM. The results can be applied for the selection of the necessary materials in the production of equipment at a known operation temperature, as well as for compromise optimization of researched parameters for quality management of composite alloys such as SAP.